Association between nocturnal blood pressure dipping and chronic kidney disease. (3rd October 2022) - Motiejunaite, J; Alencar De Pinho, N; Arnoult, F; Vrtovsnik, F; Tabibzadeh, N; Flamant, M; Vidal-Petiot, E
Abstract: Introduction: Management of blood pressure (BP) in chronic kidney disease (CKD) is critical for preventing cardio-renal complications. While increasing attention has been given to discrepancies between office and ambulatory BP control in this population, information on nocturnal BP decrease patterns (dipping) in CKD is still scarce. Purpose: We aimed at describing nocturnal BP dipping patterns and its predictors in patients with CKD. Methods: We analysed data from patients with CKD stages 1 to 5 referred for kidney function testing from September 2006 to January 2022, including 24-hour urine collection, gold-standard measurement of glomerular filtration rate (GFR) using clearance of a radioisotopic tracer, as well as ambulatory BP measurement (ABPM) in a single tertiary hospital in Paris, France. A total of 1177 ABPM were available in 642 participants. The magnitude of dipping was calculated as the difference between day- and night-time systolic BP (SBP), in percentage of daytime SBP. Participants were then categorized as extreme-dippers (≥20%), dippers (10% to <20%), non-dippers (0% to <10%), or reverse-dippers (<0%). Factors associated with a less than 10% dipping were analysed with crude and adjusted logistic regression models including a random intercept to deal with clustering of measurements within patients. Results: Participants (mean age 56±15 years; 35% female, mean GFR 49±21 mL/min per 1.73 m 2 ) consisted of 8% extreme-dippers, 37% dippers, 40% non-dippers, and 15% reverse-dippers. The prevalence of non- or reverse-dipping increased with CKD severity, from 36% in CKD stage 1 to 65% in CKD stages 4–5 (Figure). In crude analyses, African origin, a lower measured GFR, a higher daytime SBP, diabetes, a higher number of antihypertensive medications and a higher 24-hour urinary sodium to potassium ratio (24h Na/K) were associated with abnormal dipping status. In the multivariable adjusted regression, non or reverse dipping was independently associated with measured GFR (odds ratio [OR, 95% confidence interval] per 10 ml/min/1.73 m 2 decrease = 1.16 [1.06–1.26], p=0.001), daytime ambulatory SBP (OR per 10 mmHg decrease = 1.17 [1.06–1.28], p=0.001), African origin (OR= 1.56 [1.04–2.34], p=0.03) and 24h Na/K (OR per 1-unit increase = 1.20 [1.06–1.37], p=0.006). Conclusions: The prevalence of nocturnal non-or reverse dipping BP profiles increases substantially across the spectrum of CKD. Measured GFR, ambulatory daytime SBP, African origin and 24-hour urinary sodium to potassium ratio are independent predictors of abnormal nocturnal BP decrease and thus may help in cardiovascular risk stratification in this population. More research is needed on whether nocturnal dipping may be a treatment target to reduce cardiorenal complications. Funding Acknowledgement: Type of funding sources: None.